ISLAMIC PHILOSOPHY AS A CIVILIZATION OF EVIDENCE AND CLASH OF PROOFS - DR. MÜFİT SELİM SARUHAN (Hamdard Islamicus, 2022)
This article intends to examine the role of evidence and its logic within Islamic Philosophy. Islamic Philosophy, as an essential part of Islamic thought, is a discipline that is variant from Kalam, Sufism, and Fiqh. What distinguishes Islamic Philosophy from other Islamic sciences is its unique epistemological base. Islamic philosophers used and developed many logical arguments and proofs throughout history. When these evidences are analyzed, it can be seen that the motivation behind the use of evidence in the system of Islamic philosophers can be divided into three categories. Firstly, some of the evidence is organized to illustrate and understand philosophical issues. Secondly, some of the evidence is created and formed by philosophers as they are critical and reasonable. Thirdly, in author’s opinion, another reason behind the importance of evidence in Islam is to show philosophical ability and originality. While establishing their thought systems and processing their ideas, philosophers have relied on both knowledge and the science of logic involving various argumentations. In this article, we will shed light on Islamic thought as a civilization of knowledge that is rich in terms of evidence and argumentations. In this study, the problem was handled with an inductive approach. Islamic thought is a civilization of knowledge, which also contains rich evidence. Those who mention that Islamic thought is a dogmatic system from time to time with prejudice seem to approach the issue with a perspective that is far from comprehensive analysis and composition. This study shows that the Holy Qur’an, which is the main source of Islamic thought.